2D Optical Fiber Wave Guide Design for Multi Haul Applications - Venkata Raghavendra Miriampally (Institute of Advanced Engineering and Science, 2016)
The optical communications had an exponential growth over the last few years, having a significant commercial market in optical systems and components. This growth has been extended across all application areas, from transcontinental and transoceanic distances to regional networks and lastly to campus and building wiring. This paper basically explains the concept of Optical fiber communication, the propagation of light inside the fiber and mainly the two dimensional design of optical fiber itself. The researcher discusses the parameters such as effective group delay, dispersion. Modes, Bending Loss, Material Loss, Mode field, Birefringence, Splice Loss, Polarization Mode Dispersion (PMD), Effect of nonlinear Refractive Index. Finally we design the optical fiber with all the above mentioned parameters.